2018
DOI: 10.1039/c7ra13418e
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide-supported Ag-loaded Fe-doped TiO2 for the degradation mechanism of methylene blue and its electrochemical properties

Abstract: Graphene oxide-based composites have been developed as cheap and effective photocatalysts for dye degradation and water splitting applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Also, Jaihindh et al . [99] reported a k app value of 8.7 × 10 −3 min −1 for visible light photocatalytic degradation of MB after 150 min using GO-supported Ag-loaded Fe-doped TiO 2 as photocatalysts. Sohail et al [100] also reported a k app value of 12.2 × 10 −3 min −1 for photocatalytic degradation of MB after 120 min under UV light irradiation using TiO 2 -reduced GO nanoparticles as photocatalyst.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Jaihindh et al . [99] reported a k app value of 8.7 × 10 −3 min −1 for visible light photocatalytic degradation of MB after 150 min using GO-supported Ag-loaded Fe-doped TiO 2 as photocatalysts. Sohail et al [100] also reported a k app value of 12.2 × 10 −3 min −1 for photocatalytic degradation of MB after 120 min under UV light irradiation using TiO 2 -reduced GO nanoparticles as photocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Yang et al[98] reported a k app value of 3.3 Â 10 23 min 21 for photocatalytic degradation of MB after 180 min using poly-o-phenylenediamine-modified TiO 2 nanocomposites as photocatalysts. Also, Jaihindh et al[99] reported a k app value of 8.7 Â 10 23 min 21 for visible light photocatalytic degradation of MB after 150 min using GO-supported Ag-loaded Fe-doped TiO 2 as photocatalysts. Sohail et al[100] also reported a k app value of 12.2 Â 10 23 min 21 for photocatalytic degradation of MB after 120 min under UV light irradiation using TiO 2 -reduced GO nanoparticles as photocatalyst.…”
mentioning
confidence: 99%
“…The PL peak located at the 526 nm is related with the shallow trap on surface oxygen vacancies of TiO 2 [59]. It has been clearly found that the PL intensity decreases from sample ST1 to ST3 with increasing Sn content in TiO 2 because of generated electron-hole pair can affect the charge transfer between the interface of Sn and TiO 2 resulting recombination rate is reduced.…”
Section: Resultsmentioning
confidence: 93%
“…A small decrease in the peak intensity of nanocomposite can be seen, indicating larger separation of electron and holes. When CeO 2 (electron donor) interacts with rGO, it transfers the excited electrons to the rGO (electron acceptor), which lead to a reduction in the recombination rate of electron‐hole pairs, and therefore a greater number of charge carriers can participate in the photocatalytic degradation of MB and CR dyes …”
Section: Resultsmentioning
confidence: 99%